â€œ TRACING METHOD PROFIT SHARING TO FINANCING MUDHARABAH PT. BTN SYARIAH BRANCH MALANGâ€ - Hadibowo, Alfan Eko; Mulawarman, Aji Dedi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
The goal of this research is to know application of Mudharabah which based on Revenue Sharing, and to know the reason of Revenue Sharing which used in PT. Bank Tabungan Negara Syariah Malang. This research is classified into qualitative research which use descriptive method with case study approach. This research will describe the real situation to know and analyze the problems which experienced by research object. Based on the result, researcher found that Revenue Sharing is applied by PT. Bank Tabungan Negara Syariah Malang in Mudharabah. The reason of that are, (a) To be honest people is rare in Indonesian culture, (b) Difficult to supervise the calculation and analyses of customer burdenâ€™s, (c)To avoid possibility of Moral Hazard from customer. It means customer tends to say that the business was loss in the report to make the sharing profit with bank become little, (d) Still be guided on PSAK no. 59, (e) The sharing profit on Mudharabah will more favorable for the bank, (f) BTN Syariah is one of BTN units which still oriented on benefit, and (g) The assumption of Branch Manager BTN Syariah Malang which assumes that they just do the instruction from the head office. Â Keywords :Syariah Bank, Mudharabah, Revenue Sharing